If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 9 = 7x + -63 Reorder the terms: 9 + x = 7x + -63 Reorder the terms: 9 + x = -63 + 7x Solving 9 + x = -63 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + x + -7x = -63 + 7x + -7x Combine like terms: x + -7x = -6x 9 + -6x = -63 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + -6x = -63 + 0 9 + -6x = -63 Add '-9' to each side of the equation. 9 + -9 + -6x = -63 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = -63 + -9 -6x = -63 + -9 Combine like terms: -63 + -9 = -72 -6x = -72 Divide each side by '-6'. x = 12 Simplifying x = 12
| y-10=2 | | 6x^2-7x-5=0 | | 3x^2+x=2x-6 | | 3+(-5x)=-17 | | y=94+5(1-9) | | 4(a+3.2)=9a-5.2 | | y=9+5(1+8) | | 4x-5+5x-15=180 | | 6(-4-7a)+4=28+6a | | 2x^2-3x=20 | | 6b-2b+6=-10 | | 205=5(1+5v) | | 8-4d=12 | | y=8+6(1-5) | | -35+7x=8(x-4) | | 2[a-1]=3[a+1] | | 9a-(15a-(3b+7a)+(-8b+a)+12b)= | | y=5+5(1-8) | | 7(x+5)-4=87 | | .6(2m-10)=.6m+10 | | 12-4y=16x | | y=-25+4(1+5) | | y=10+3(1-5) | | y=-13+4(1+2) | | h=-16t^2-10t+130 | | y=30-2(1+3) | | -3x+6=-4x-5 | | 2x-(-3x+5y)+(-5x-6y)= | | 7x=-28 | | 7[g-4]=3 | | 5(5x-3)=6(4x+1) | | y=14-2(1-5) |